On the research and design of automobile hinge production logistics system based on extensive flow. (1st January 2013) - Dong, Yude; Wang, Linglan; Sun, Qinqin; He, Xien; Hu, Cunmei; Wu, Zhong; Hu, Maochang; Yao, Yi; Shen, Shoufeng
Automobile hinge production is primary in the chain of automobile manufacturing. In order to inform and standardise production, extensive flow has been introduced to productive procedure. This paper briefly reviews manufacturing logistics system from both theoretical and executive aspect. It also discusses Anhui Jiangnan mode. It evaluates how an elaborated system works for products. Automobile hinge production logistics system with extensive flow helps not only massive production but also budget control. It is suggested to solve inconsistency and inefficiency in manufacture and distribution process.